A novel equation synthesis for estimating resting energy expenditure in prostate cancer patients - Nilüfer Acar Tek; Tevfik Koçak; Süleyman Yeşil; Tevfik Sinan Sözen (BMC Urology)
Abstract Background An accurate calculation of energy expenditure (REE) is necessary for estimating energy needs in malign prostate cancer. The purpose of this research was to evaluate the accuracy of the established novel equation for predicting REE in malign and benign prostate patients versus the accuracy of the previously used predictive equations based on REE measured by indirect calorimetry. Methods The study was conducted as a cross-sectional case-control study and between December 2020 and May 2021 with 40 individuals over the age of 40 who applied to the Urology Clinic of Gazi University Faculty of Medicine. Subjects with 41 malign prostate and 42 benign prostate patients were both over the age of 40 (65.3 ± 6.30 years) and recruited for the study. Cosmed-FitMate GS Indirect Calorimetry with Canopyhood (Rome, Italy) was used to measure REE. A full body composition analysis and anthropometric measurements were taken. Clinical trial number: Not applicable. Results Malign prostate group PSA Total and measured REE values (4.93 ± 5.44 ng/ml, 1722.9 ± 272.69 kcal/d, respectively) were statistically significantly higher than benign group (1.76 ± 0.73 ng/ml, 1670.5 ± 266.76 kcal/d, respectively) (p = 0.022). Malign prostate group (MPG) and benign prostate group (BPG) have the highest percentage of the accurate prediction value of Eq. 80.9% (novel equation MPG) and 64.2% (novel equation BPG). The bias of the equations varied from − 36.5% (Barcellos II Equation) to 19.2% (Mifflin-St. Jeor equation) for the malign prostate group and varied from − 41.1% (Barcellos II Equation) to 17.7% (Mifflin-St. Jeor equation) in the benign prostate group. The smallest root mean squared error (RMSE) values in the malign and benign prostate groups were novel equation MPG (149 kcal/d) and novel equation BPG (202 kcal/d). The new specific equation for malign prostate cancer: REE = 3192,258+ (208,326* body weight (WT)) - (20,285* height (HT)) - (187,549* fat free mass (FFM)) - (203,214* fat mass (FM)) + (4,194* prostate specific antigen total (PSAT)). The new specific equation for the benign prostate group is REE = 615,922+ (13,094*WT). Bland-Altman plots reveal an equally random distribution of novel equations in the malign and benign prostate groups. Conclusions Previously established prediction equations for REE may be inconsistent. Utilising the PSAT parameter, we formulated novel energy prediction equations specific to prostate cancer. In any case, the novel predictive equations enable clinicians to estimate REE in people with malign and benign prostate groups with sufficient and most acceptable accuracy.